PROFITABILITY AND TAX AVOIDANCE ON COMPANY VALUE MODERATED PROFIT MANAGEMENT - Mardiana, Mardiana; Setiyowati, Supami Wahyu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Company value is the public's view or belief in a company. A high company value indicates that the company's performance is good. Good performance will have an impact on future prospects that can be trusted by investors and the public. This study is to examine the influence of profitability, and tax avoidance on the value of companies moderated by profit management. This type of research is quantitative research. The study population is food and beverage companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Sampling techniques based on cretaria. The number of samples in this study is 60. The data analysis technique uses Moderated Regression Analysis (MRA). The results of the study show that profitability and tax avoidance affect the value of the Company. Profit management moderates the relationship between profitability and tax avoidance to the value of the Company. The implication of this research is that tax avoidance and profit management can be carried out by companies within reasonable limits can increase the value of the company. The novelty of this study uses profit management as a moderation of the relationship between tax avoidance and profitability to company value.